Demographic Characteristics and the Performance of Supervisors of Swallowing Drugs in Parepare, Indonesia - Syarifuddin Syarifuddin; Chatarina Umbul Wahyuni; Soenarnatalina Melaniani (Humanistic Network for Science and Technology (HNST), 2018)
2, 3 1(CA), Indonesia; (Corresponding Author) 2, Indonesia 3, Indonesia ABSTRACT Pulmonary tuberculosis is a disease of global concern. This research was carried out in the work area of the City Health Center in Parepare, South Sulawesi, Indonesia. The purpose of this study was to analyze the influence of characteristics of supervisors swallowing drugs participants including demographic characteristics (age, sex, education, socio-economic), knowledge, attitudes and practices; on the performance of